Convergence to the Managerial Frontier - William F. Maloney; Mauricio Sarrias (Institute for the Study of Labor (IZA), 2014)
Using detailed survey data on management practices, this paper uses recent advances in unconditional quantile analysis to study the changes in the within country distribution of management quality associated with country convergence to the managerial frontier. It then decomposes the contribution of potential explanatory factors to the distributional changes. The US emerges as the frontier country, not because of on average better management, but because its best firms are far better than those of its close competitors. Part of the process of convergence to the frontier across the development process represents a trimming of the left tail, much is movement of the central mass and, for rich countries, it is actually the best firms that lag the frontier benchmark. Among potential explanatory variables that may drive convergence, ownership and human capital appear critical, the former especially for poorer countries and that latter for richer suggesting that the mechanics of convergence change across the process. These variables lose their explanatory power as firm and average country management quality rises. Hence, once in the advanced country range, the factors that improve management quality are less easy to document and hence influence.
Keywords: C21; L2; M2; O33; O47; 330; management practices; convergence; development; quantile regression; RIF decomposition